High-Throughput Flow Cytometry Drug Combination Discovery with Novel Synergy Analysis Software, SynScreen. (August 2018) - Perez, Dominique R.; Edwards, Bruce S.; Sklar, Larry A.; Chigaev, Alexandre
Classical therapeutic regimens are subject to toxicity, low efficacy, and/or the development of drug resistance. Thus, the discovery of synergistic drug combinations would permit treatment with lower, tolerable dosages of each agent and restored sensitivity. We describe the development and use of the SynScreen software application, which allows for visual and mathematical determinations of compound concentrations that produce super-additive effects. This software uses nonlinear regression fits of dose responses to determine synergism by the Bliss independence and Loewe additivity analysis models. We demonstrate the utility of SynScreen with data analysis from in vitro high-throughput flow cytometry (HTFC) combination screens with repurposed drugs and multiplexed synergy analysis of multiple biologic parameters in parallel. The applicability of SynScreen was confirmed by testing open-source data sets used in published drug combination literature. A key benefit of SynScreen for high-throughput drug combination screening is that observed measurements are graphically depicted in comparison with a three-dimensional surface that represents the theoretical responses at which Bliss additivity would occur. These images and summary tables for the calculated drug interactions are automatically exported. This allows for substantial data sets to be visually assessed, expediting the quick identification of efficacious drug combinations and thereby facilitating the design of confirmatory studies and clinical trials.